Analgesic effect of indomethacin shown using the nociceptive flexion reflex in humans. Issue 3 (March 1992) - Guieu, R; Blin, O; Pouget, J; Serratrice, G
Abstract : This study investigated whether indomethacin has an analgesic effect on the central nervous system. As analgesics which affect the central nervous system produce a correlated decrease in the subjective sensation of pain and in the nociceptive reflex in humans, the amplitude of the nociceptive flexion of the biceps femoris was studied. Eight patients (six men, two women) aged 35-70 years (mean 51) with rheumatic diseases were included in the study. Each patient was his or her own control and was given a single intramuscular injection of either 50 mg of indomethacin or a placebo. A placebo controlled, double blind experimental design was used. Patients were evaluated before and 30, 60, and 75 minutes after the injection. Seventy five minutes after injection, indomethacin gave a 54% decrease in the amplitude of the nociceptive reflex, whereas the placebo produced a decrease of only 12%. This suggests that indomethacin exerts a depressive effect on the amplitude of the nociceptive reflex and affects the central nervous system as part of its analgesic action.